Jejak Arsitektur Indische yang Hilang di Kawasan Pelabuhan Makassar - Nahridzah Mahjubuh Shiber; Ahmad Nadhil Edar (Universitas Muslim Indonesia, 2026)
This study examines the loss of Indische architecture in the port area of Makassar, tracing historical visual evidence and key records relating to Passerstraat, now known as Jalan Nusantara, and Wilhelminastraat. The analysis focuses on three documented buildings: De Javasche Bank, the Nederlandsche Handel Maatschappij and Koninklijke Paketvaart Maatschappij (KPM) building. The method combines a historical reading with an analysis of the architectural elements of massing, façade composition, and openings, as observable in historical photographs. The findings suggest that the primary pattern of loss in the studied cases is the physical disappearance of buildings, which disrupts typological data and weakens the reconstruction of the Indische period in the port environment. By treating lost buildings as legitimate architectural evidence, this study provides a more accurate estimation of the extent of the loss, indicating that the Indische presence in Makassar historically extended beyond what is visually discernible today.